# ﻿Leibniz Rule for Differentiating Products

Formula to find a high order derivative of product. Example:

d9 d9 d d8

dx9 (x sin x) = x dx9 (sin x) + 9 d)x) dx8 (sin x)

9.8 d2 d7

+ 2! dx2 (x) dx7 (sin x) + ...

d9 d8

= x dx9(sinx) + 9 dx8(sinx)

9.8 d7

+ 2! ·0· dx7(sinx)

= x cos x + 9 si n x

Leibniz Rule for Differentiating Products

Binomial expansion

Exercise: Try to differentiate this

Rodrigues' Formula

Another way of finding Legendre Polynomials

[J ~ • - •• -=. -== ",)C\.C"

Rodrigues' Formula: Cont'd Example: when 1=0

When 1=1

When 1=2

1 d2 2 2

P2(X) = 2221 dx2 (x - 1)

1 2 1 2

= -(12x - 4) = -(3x - 1)

8 2

Rodrigues' Formula: Proof

Let v = (X2 - I)'. Differentiate once

dv = l(x2 _ 1)'-1(2x) dx

2 dv 2

(x - 1) dx = I(x - 1)(2x) = I· v . 2x

2 dv

(x - 1) dx = 2xlv (1)

Rodrigues' Formula: Proof Cont'd

Differentiate Eqn. (1) 1 + 1 times using Leibniz rule

d'+l ( dV) d'+l

dx'+l (x2 - 1) dx = dx'+l (2xlv)

2 d'+2v d'+lv (I + 1)/ d'v

(x -1) dx'+2 + (I + 1)(2x) dx'+l + 2! ·2· dx'

d'+lv d'v

= 2/x dx'+l + 21(1 + 1) dx'

(2)

Rodrigues' Formula: Proof Cont'd

Rearrange Eqn. (2), we get

Which show that the Rodrigues' formula satisfied the Legendre equation.

Rodrigues' Formula: Proof Cont'd

Here we see that

d'v

c· dx' = P,(x)

The derivative for x2n, when v = (x2 - I)' = (x + 1)'(x - I)' is

d'v d' d'-1

" '-I ,

dx' = (x + 1) dx' + c1· I(x + 1) . dx'-1 (x - 1)

, d' ,

+···+(x-l) dx,(x+l) =0

When x = I,

d'v = 2' ./1 dx/ .

Rodrigues' Formula: Proof Cont'd

Thus, when x = 1

Which give C as

So,

Proved

[J ~ • - •• -=. -== ",)C\.C"

Generating Function for Legendre Polynomials

Many properties of Legendre Polynomials can be derive by using Generating function

¢> (x h) = ----;====1====;;::

, VI - 2xh + h2 '

Ihl < 1,

(3)

Generating Function for Legendre Polynomials: Cont'd

Maclaurin series for (1 - y)-1/2 for -1 < y < 1 is

Setting y = 2xh - h2, we obtain

1 1 2 3 22

---;========;;;: = 1 + -(2xh - h ) + -(2xh - h )

VI - 2xh - h2 2 8

15 105

+ -(2xh - h2)3 + -(2xh _ h2)4

48 384

945 2 5

+ 3840 (2xh - h) + ...

Generating Function for Legendre Polynomials: Cont'd

Expand the previous equation and collecting h term, we get

00

Generating Function for Legendre Polynomials: Cont'd

When x = 1

<1:>(1, h) = (1 - 2h + h2)-1/2 1

1-h

= 1 + h + h2 +.

== Po(l) + P1(1)h + P2(1)h2 + ...

Generating Function for Legendre Polynomials: Cont'd

To show that generating function satisfy Legendre equation, we use this equation

Where

8<1:>

h

8x (1 - 2xh + h2)3/2

82<1:> 3h2

8x2 (1 - 2xh + h2)5/2

82 h<l:> _ _ -2x + hx2 - 2xh2 + 3h

8h2 ( ) - (-1 + 2xh - h2)v1 - 2xh + h2

Generating Function for Legendre Polynomials: Cont'd

Inserting

00

1=0

into the previous equation, we get

00

00

00

1=0

1=0

1=0

00

L hi ((1 - x2)p;' (x) - 2xP;(x) + /(1 + l)PI(x)) = 0

1=0

Which is Legendre Equations.

Recursion Relations for Legendre Polynomials

1. IP,(x) = (2/- l)XP'_l(X) - (! - 1)P,_2(x)

2. xP;(x) - P;_l(X) = IP,(x)

3. P;(x) - XP;_l(X) = IP'_l(X)

4. (1 - x2)P;(x) = IP'_l(X) - IxP,(x)

5. (21 + l)P,(x) = P;+l(x) - P;_l(x)

6. (1 - x2)P;_1(x) = IXP'_l(X) - IP,(x)

Proof for IPt(x) = (21 - 1)xPt-1(x) - (! - 1)Pt-2(x)

Given

00

<I:>(x, h) = (1 - 2xh + h2)-1/2 = L h' P,(x)

'=0

We differentiate with respect to h,

1

~====::::::==:==:;:=;;;:( -2x + 2h)

8h 2~1 - 2xh + h2

8<1:>

(1 - 2xh + h2) 8h = (x - h)<I:>

8<1:>

Or

00 00

(1 - 2xh + h2) L Ih'-l P,(x) = (x - h) L h' P,(x)

'=1

'=0

Proof for IPt(x) = (21 - 1)xPt-1(x) - (! - 1)Pt-2(x):

Cont'd

Expanding the previous equation, we get,

00

00

00

1=1

1=1

1=1

00

00

= x L hi PI(X) - L hl+1 PI(X)

1=0 1=0

Adjusting h indices so that all become hi-I, we get

00

00

00

1=1

1=2

1=3

00

00

1=1

1=2

Proof for IPt(x) = (21 - 1)xPt-1(x) - (! - 1)Pt-2(x):

Cont'd

We can write the equation from the previous slide as

When we rearrange we will get the first recursion formula.

Given

00

<I>(x, h) = (1 - 2xh + h2)-1/2 = L hi P/(X) 1=0

Differentiate with respect to h, we get

8<1> = (x - h) = ~ Ihl-lp (x) (4)

8h ~1 - 2xh + h2 ~ I

Differentiate with respect to x, we get

8<1> 8x

1 ( 2h)

2~1 - 2xh + h2

_ h -~hlp'(x)

- ~1 - 2xh + h2 - ~ I

(5)

Dividing Eqn. (4) with Eqn. (5), we get

x-h h

00

00

00

1=0

1=0

1=0

00

Adjusting h indices so that all become hi, we get

00

00

1=0 1=0

00 00

1=0

1=1

00

So we get the second recursion relation

The first recursion relation is

Differentiate with respect to x, we get

Rearrange, using second recursion relation, we get

I[P; - XP;_l]- (I - l)[XP;_l - P;-2] = I[P; - XP;_l] - (I - 1)[(1 - l)P'-l] = (2/- l)P'-l

Then

I[P; - XP;_l] = (I - 1)(1 - l)P'-l + (21 - l)P'-l = PP'-l

So we get the third recursion relation.

Using

P;(x) - XP;_l(X) = IP'_l(X) XP;(X) - P;_l(X) = IP,(x)

(6) (7)

Multiply Eqn. (7) with x and subtracting from Eqn. (6), we get

Using first recursion relation

Replacing 1 with 1 + 1, we get

(I + l)P'+l = (2(1 + 1) - l)xP, - (I + 1 - l)P'-l = (21 + l)xP, - IP'-l

Differentiate with respect to x, we get

Inserting the second recursion formula xP; - P;-l = IP, into the previous equation, we get

(! + l)P;+l = (21 + l)P, + (21 + l)(!P, + P;-l) - IP;_l (! + l)P;+l - (! + l)P;_l = (21 + 1)(1 + I)P,

So we get

Try to prove this recursion relation on your own.

Sign up to vote on this title